Lactic Acid Bacteria (LAB) with Probiotic Potential from Dengke Naniura (Baghdad Science Journal, 2021)
Dengke Naniura is a traditional food from Sumatera Utara, Indonesia, that is produced through fermenting process, and this food is believed to contain high probiotics. The objective of the current research is to determine the potential of LAB as a probiotic that has been obtained from Dengke Naniura. Dengke Naniura was traditionally prepared from Cyprinus carpio. Four LABs have been successfully isolated from Dengke Naniura, such as D7DA3, D7B3, D7DBF and D7DN3. Those four LAB isolates were identified as Lactobacillus sp. This result has been confirmed by the non-spore forming bacterium, non-motile, and Gram-positive. Also, it has been supported by biochemical test, for the example Voges Proskauer, catalase test, Methyl Red test, and carbohydrate fermentation. Several tests have been performed for determining the properties of the isolated LABs as probiotic, for the example: physiological properties, acid and bile tolerance and antimicrobial activities. As a probiotic, the fermentation profile of the isolated LAB was evaluated, including titratable acidity, pH, and organoleptic test. The all four isolates show the ability to survive in the MRS broth medium at pH 2 and 3. At the pH 3, the isolates of D7B3 show the highest ability to survive; it is about 100%, after 2 hours of incubation time. This data is followed by D7DBF4 with value 90 and 24% at pH 3 and 2, respectively. Otherwise, the isolate of D7DN3 and D7DA3 shows the lowest value, it is about 55-58% and 52-58% at pH 3 and 2, respectively. The fermented milk has been successfully made from LAB that has been isolated from Dengke Naniura. The fermented milk prepared using D7DA3 and D7DN3 has consistence and odor as similar as yoghurt, otherwise the isolate of D7DB3 and D7DBF4 produced fermented milk that is too thick. The fermented milk prepared from these isolates, D7DA3, D7DBF4 and D7DN3 has a normal taste. The better taste has been obtained in the fermented milk that was prepared using D7B3 isolate. The fermented milk prepared using LAB and obtained from Dengke Naniura has titratable acidity of 0.92-1.15% with pH 4.03-4.60.